Correction: Baseline Omega-3 Index Correlates with Aggressive and Attention Deficit Disorder Behaviours in Adult Prisoners. - Barbara J Meyer; Mitchell K Byrne; Carole Collier; Natalie Parletta; Donna Crawford; Pia C Winberg; David Webster; Karen Chapman; Gayle Thomas; Jean Dally; Marijka Batterham; Ian Farquhar; et al. (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0120220.].